Kobciye: empowering Somali refugees in Nairobi - Hassan, A (Refugee Studies Centre, University of Oxford, 2018)
Established by a resettled Somali refugee and now under the leadership of his children, Kobciye resource centre works to empower Somali refugees in Eastleigh, Nairobi.